Scientometric analysis of the publication output of the department of mathematics in NUS. - Ng, Cheng Soon. (2008)
This study objective is to examine the productivity and authorship patterns of one of the oldest departments, in NUS by subjecting the articles published and other documents to scientometric and bibiliometric analysis.